FAKTOR-FAKTOR RISIKO MALARIA DI WILAYAH KERJA PUSKESMAS PARUGA KOTA BIMA NUSA TENGGARA BARAT - Rubianti, Irma; Wibowo, Trisno Agung; Solikhah, Solikhah (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2009)
Background: Malaria is one of reemerging diseases and ranked in 10th position as deadly diseases. Malaria is also the 5thdeadly infective disease in the world. Malaria is tropical disease that been main cause of death, each year 40% of world inhabitant have risk of malaria disease or approximately 300 500 million of cases. About 1 3 millions of people died because of malaria each year. In Indonesia, about 50% of Indonesian people live in malaria endemic area. According to WHO, not less than 30 million cases of malaria occurs each year in Indonesia about 30.000 people were died.This study is purposed to recognize risk factors in relation with malaria incident in working area of Paruga Puskesmas (Public Health Service), Bima City, of Nusa Tenggara Barat.Methods: This was analytic-observational research using case-control approach. Sampling was performed in a way of purposive sampling. Cases in this study were malaria sufferer, who takes medical care in Puskesmas of Paruga and those who counted to Mass Blood Survey program on May, 2008. Control was another diseases sufferer who takes medical care in Puskesmas of Paruga and not suffers malaria according to Mass Blood Survey as shown in laboratory examination result.Results: There was relation between distance of house, mosquitos propagation place as well as mosquitos shelter and malaria incident as seen from OR=5,41, CI=1,38<OR<24,81, p=0,001. There was no relation between habit of setting mosquito net and malaria incident as seen from OR=1,00, CI=0,52<OR<1,94, p=1,00. There was relation between habit of setting mosquito essence and malaria incident as seen from OR= 2,25, CI=1,05<OR< 3,88, p=0,023. There was no relation between habit of going out at night and malaria incident as seen from OR=1,67, CI=0,73<OR<3,82, p=0,184. There was relation between knowledge and malaria incident as seen from OR=1,99, CI=1,02<OR<3,88, p=0,029. There was no relation between malaria elucidation and malaria incident as seen from OR=0,94, CI=0,43<OR<2,03, p=0,855.Conclusion: Distance of house, mosquitos propagation place as well as mosquitos shelter, habit of setting mosquito net, and knowledge was malaria risk factors in working area of Paruga Puskesmas (Public Health Service), Bima City, of Nusa Tenggara Barat.Keywords: Risk factors, malaria, Puskesmas of Paruga (Paruga Public Health Service)